Mussolini's army in the French Riviera : Italy's occupation of France - Sica, Emanuele, 1975- (History of military occupation., 2016)
"Following the conquest of Europe during the WWII, the Axis powers implemented occupation policies, often savage and brutal, to consolidate their European empire. After the war, a myth of Italiani Brava Gente (Italians, good fellows) perpetuated the belief that Italian soldiers were essentially good-natured and, unlike the German forces, incapable of perpetrating massacres against local civilians. In this study, Emanuele Sica examines the Italian military occupation of the French Riviera and Alpine region from June 1940 to September 1943, with particular attention to the relationship between Italian soldiers and the local population. The Italian occupation policy in France, unlike the one in the Balkans, was moderate and low in casualties. This mild approach to occupation of foreign soil was due in part to pragmatic reasons. Italian local commanders understood that softening their occupation policy was the best means of preventing the formation of partisan groups in the area. In fact, the Italians' strategic nightmare would have been an Allied seaborne invasion from the Mediterranean while concurrently fighting a Resistance uprising in France. Confronted with overstretched lines, pervasively poor morale within the ranks of the Italian occupation army in France and outdated materiel, the local command avoided harsh measures that could drive the French population towards resistance. However, Sica also asserts that the cultural proximity between the soldiers and the local population, 1/4 of which was Italian, played an important role in positively shaping the relationships between occupiers and occupied, smoothing the sharp angles of miscommunication and minimizing inevitable cultural faux-pas at a time of great uncertainty and tension"--